Synergistic Effects of Thermal Stress and Estuarine Discharge on Transcriptomic Variation of Montastraea cavernosa Corals in Southeast Florida - Studivan, Michael S.; Shatters, Alycia; Dodge, Danielle L.; Beal, Jeff L.; Voss, Joshua D. (Frontiers in Marine Science, 2021)
Coral reefs at the northern extent of Florida’s coral reef tract are exposed to many localized anthropogenic influences including controlled freshwater discharges, runoff, upwelling, and seasonal environmental variability. To better understand coral responses to sublethal stressors in nearshore environments, we conducted complementary experiments to assess the impacts of estuarine runoff and temperature stress on local populations of the scleractinian coral species, Montastraea cavernosa, using Tag-Seq global gene expression profiling. In an in situ time series experiment, fate-tracked colonies were sampled during periods of relatively low and high estuarine discharge over 4 years to investigate temporal trends in transcriptional patterns and to identify if coral stress indicators were regulated through time. There was significant transcriptomic variation through time, but patterns did not appear to be attributed to distance from nearby estuarine tidal flux. In an ex situ factorial experiment, clonal replicates of coral genotypes were exposed to temperature (25°C and 30°C) and water (offshore and estuarine discharge, representing typical oceanic conditions and episodic discharge conditions, respectively) treatments to quantify the potential individual and synergistic effects of sublethal stress on coral and algal gene expression. Comparative analyses suggested that corals and their algal symbionts were more responsive to thermal stress than to estuarine discharge, although there was evidence of a synergistic relationship between the two stressors. Strong genotype effects also demonstrated that transcriptomic responses to thermal stress were largely based on coral genotype, indicating the potential for stress resilience among certain members of coral populations from southeast Florida.